XANTHONES FROM Hypericum laricifolium Juss., AND THEIR ANTIPROLIFERATIVE ACTIVITY AGAINST HEP3B CELLS - Morales Moisela, Marlon Miguel (2018)
We describe here the isolation of 6 xanthones and one phenyl-γ-pyrone, together with 3-epibetulinic and quercetine from the aerial parts of Hypericum laricifolium Juss. (Hypericaceae), collected in Peru. Isolated compounds have been evaluated against proliferation of human hepatocellular carcinoma Hep3B cells. The most active compound was xanthone 3, with an inhibitory concentration (IC50) of 12 µM.